“AKSIOLOGI PACKAGING” PERSPEKTIF SMALL BISNIS AND CUSTOMER DI SIDOARJO - Putu Suardana, I Gede; Ratnawati, Tri; Kusmaningtyas, Amiartuti (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2019)
During this time, the business actors in the Small Business, lack of understanding about Packaging, especially regarding the functions and benefits, so they make thePackaging with the origin. This study aims to determine the role and function ofpackaging in maintaining product safety, as a promotional media so as to increase theselling value of the products of the Small Business. Appropriate material structure,attractive packaging appearance will give a distinct impression for consumers indetermining their decision to buy or not buy a product. Descriptive qualitative researchmethod by conducting a direct survey of Small Business in Sidoarjo, and also conductinglibrary and literature studies. The results of this study prove that the right materialstructure and the appearance of packaging that is very attractive to consumers willincrease sales of these Small Business products.Keywords: Packaging, product sale small business product